2015
DOI: 10.1016/j.socscimed.2015.02.006
|View full text |Cite
|
Sign up to set email alerts
|

The impact of neighborhood quality, perceived stress, and social support on depressive symptoms during pregnancy in African American women

Abstract: Living in a lower-quality neighborhood is associated with higher levels of depressive symptoms in the general population as well as among pregnant and postpartum women. However, little is known of the important pathways by which this association occurs. We proposed a model in which perceived stress and social support mediated the effects of neighborhood quality on depressive symptoms during pregnancy (measured by the 20-item Center for Epidemiologic Studies-Depression, CES-D, scale) in a sample of 1383 African… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
90
2
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(108 citation statements)
references
References 77 publications
7
90
2
9
Order By: Relevance
“…This finding was consistent with the results of many other studies like Giurgescu et al and Morikawa et al, they found that mothers who enjoyed adequate social support during pregnancy experienced have a healthier pregnancy compared to those who did not have (42,43). Family and husband support during pregnancy may effect on maternal and fetal health through unmeasured mediators such as improved maternal health behaviors (refraining from smoking and drinking, etc.…”
Section: Discussionsupporting
confidence: 91%
“…This finding was consistent with the results of many other studies like Giurgescu et al and Morikawa et al, they found that mothers who enjoyed adequate social support during pregnancy experienced have a healthier pregnancy compared to those who did not have (42,43). Family and husband support during pregnancy may effect on maternal and fetal health through unmeasured mediators such as improved maternal health behaviors (refraining from smoking and drinking, etc.…”
Section: Discussionsupporting
confidence: 91%
“…For example, researchers might adapt a self-directed humility workbook intervention developed for college students (Lavelock et al, 2014) for use with couples becoming new parents. Based on the results of our study, such an intervention might help couples cope with the stressors of transitioning into parenthood-including role changes, financial burden, and lower perceived social support (Giurgescu et al, 2015;Perren et al, 2005;Twenge et al, 2003)-in other-oriented rather than self-focused ways.…”
Section: Implications For Relational Humility As Couples' Transition mentioning
confidence: 97%
“…Both partners must adjust to having less time, energy, and cognitive capacity to remain responsive to each other's needs (Crnic & Low, 2002;Kluwer, 2010;Twenge, Campbell, & Foster, 2003). Typical stressors include (a) role changes when many women become the primary caregiver and many men carry more financial burden; (b) decreases in perceived freedom because parents responsibly focus on the infant; (c) decreases in sexual intimacy; (d) financial stress and medical conditions that impact the mother's health; and (e) lack of social support (Giurgescu et al, 2015;Perren, von Wyl, Bürgin, Simoni, & von Klitzing, 2005;Twenge et al, 2003).…”
Section: The Transition To Parenthoodmentioning
confidence: 99%
“…Disadvantaged urban neighborhood . African-American women Characteristics of a disadvantaged neighborhood, including poverty, unemployment, and violence, may lead to increased chronic stress [1,2], susceptibility to depression [3], and PTSD [4]. The rate of depression (36%) is at least twice as high [5,6] and the rate of post-traumatic stress disorder (PTSD) is higher (~23 vs. 10%) among women in disadvantaged neighborhoods than women from the general population [7,8].…”
mentioning
confidence: 99%